TEORI KEBUDAYAAN DAN IMPLIKASINYA PADA PENDIDIKAN - Legimin Legimin; Feriansyah Feriansyah; Ubabuddin Ubabuddin (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Learning is a process of acculturation, in the sense that learning becomes a vehicle for the transmission of scientific culture and the culture of national life to students as the next generation, the adoption of scientific culture and the culture of community life by students, as well as the development of culture within a community. However, learning itself has cultural traditions, assumptions, scientific principles, etc. which makes learning a separate cultural system. From time to time, the culture of learning has changed, along with developments in science, advances in technology, and various needs of society. And society is a collection of individuals who organize themselves into certain groups. To be a community, a particular group must have something in common that allows them to perceive each other as distinct from their own and other "similarities" that ultimately form a culture. Culture is a kind of social cement which consists of typical habits such as principles, ideals, attitudes, beliefs and ways of thinking. So the difference between society and culture is clear. Without culture there is no society, there is no community there is no culture